Hybrid Curriculum Model: Analisis Kurikulum Merdeka dan Kurikulum Kemenag (Cinta–Makkiyah) pada Satuan Pendidikan MI Tahfizh Cendekia Pekanbaru - Aulia Mar'atu Dzikra; Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the implementation of a Hybrid Curriculum Model at MI Tahfizh Cendekia Pekanbaru, which combines the national “Merdeka Curriculum” with two institution-based curricula: the Cinta Curriculum (character and worship habituation) and the Makkiyah Curriculum (Qur’an memorization). A qualitative case study was used, involving observation, interviews with principals and teachers, and documentation analysis (ATP, lesson modules, schedules). Data were analyzed using the Miles–Huberman interactive model: data reduction, data display, and conclusion drawing. Findings reveal that curriculum integration is conducted through block scheduling and alignment of learning objectives. Morning sessions are allocated for tahfizh (Makkiyah), mid-day sessions for character habituation (Cinta), and afternoon sessions for academic learning (Merdeka). This structure enables balanced learning outcomes: academic improvement in literacy and numeracy, strengthened spiritual dimension through stable memorization and worship habits, and enhanced emotional–character development such as calmness, discipline, and respect for teachers. Challenges arise in time synchronization, teacher readiness in managing three curricula, and the need for authentic assessment. These challenges are addressed through internal training, mentoring, and portfolio-based assessment. The study concludes that the Hybrid Curriculum Model allows tahfizh-based schools to maintain their Qur’anic identity while meeting national academic standards. This model may serve as a reference for other Islamic schools integrating character, spirituality, and academic excellence.